Serum thrombospondin 2 is a novel predictor for the severity in the patients with NAFLD. (20th January 2021) - Kimura, Takefumi; Tanaka, Naoki; Fujimori, Naoyuki; Yamazaki, Tomoo; Katsuyama, Takahito; Iwashita, Yuichi; Pham, Jonathan; Joshita, Satoru; Pydi, Sai P.; Umemura, Takeji
Abstract: Aim: Thrombospondins are a family of multidomain and secretory glycoproteins. Among them, thrombospondin 2 (TSP2) encoded by TSP2 gene has been reported to be involved in various functions such as collagen/fibrin formation, maintenance of normal blood vessel density and cell adhesion properties. Microarray analyses ranked TSP2 as one of the most highly up‐regulated genes in the fibrotic liver in patients with non‐alcoholic fatty liver disease (NAFLD). Since TSP2 possesses unique properties as a secretory protein, we hypothesized that hepatic TSP2 gene expression levels would be reflected in serum TSP2 levels. In this study, we examined the relationship between serum TSP2 concentrations and clinicopathological findings in NAFLD patients. Methods: One hundred and thirty NAFLD patients who had undergone liver biopsy between 2009 and 2015 were retrospectively enrolled. Serum samples were collected at the time of biopsy, and TSP2 was measured by enzyme immunoassays. Results: Serum TSP2 levels moderately correlated with ballooning (r = 0.56, P < .001) and fibrosis stage (r = 0.53, P < .001). The AUC values of TSP2 for predicting mild fibrosis (≧F1), moderate fibrosis (≧F2) and severe fibrosis (≧F3) were 0.73, 0.76 and 0.82 respectively. Additionally, NAFLD activity score (NAS) correlated best with TSP2 (r = 0.52, P < .001) compared to conventional NAFLD‐related biomarkers, such as cytokeratin 18 M30, hyaluronic acid, type IV collagen 7S, APRI and FIB‐4 index. Conclusion: Serum TSP2 levels reflected hepatocyte ballooning, fibrosis and NAS in NAFLD patients. For clinical application of serum TSP2 as a predictor of NAFLD histological activity, additional validation and mechanistic investigations are required.